Hormonal Approach for Postmenopausal Vulvovaginal Atrophy - Costa, Ana Paula Ferreira; Sarmento, Ayane Cristine Alves; Vieira-Baptista, Pedro; Eleutério, José; Cobucci, Ricardo Ney; Gonçalves, Ana Katherine (Frontiers in Reproductive Health, 2021)
Menopause is a physiological and progressive phenomenon secondary to decreased ovarian follicular reserve that significantly affects the genital tract. Although postmenopausal vulvovaginal atrophy primarily affects postmenopausal women, it is also seen in premenopausal women. The hypoestrogenic condition results in hormonal and anatomical changes, with the main symptoms, are dryness, burning and genital irritation, decreased lubrication, and urinary urgency, dysuria, and recurrent urinary tract infections. This review aims to update hormone therapy for urogenital atrophy, both local and systemic, and discuss the importance of understanding and the need for active treatment of this condition. The main therapeutic objective is the relief of symptoms, and hormonal therapy (HT) is still the most effective choice for treating clinical manifestations, despite the side effects of its use. HT should be used in an individualized way to the woman's needs and appropriate to the stage in which she is menopausal, perimenopause, or after menopause.